EFEITO DE UM PROTOCOLO HIDROCINESIOTERAPÊUTICO EM UM PACIENTE COM OSTEOARTRITE: UM PROTOCOLO HIDROCINESIOTERAPÊUTICO EM OSTEOARTRITE (Fiep Bulletin - online, 2024)
Introduction: osteoarthritis is the most common pathology among arthritis and is clinically characterized by joint pain, functional limitation and reduced quality of life. The disease may be related to inflammatory and metabolic factors, in addition to the weakening of the immune system and systemic factors, and physiotherapy exercises are recommended for its treatment, such as hydrokinesiotherapy. Objective: to evaluate the effectiveness of hydrokinesiotherapy in patients with osteoarthritis. Methodology: the patient was assessed using the WOMAC questionnaire. The parameters analyzed were pain intensity, muscle stiffness and functionality. To assess pain, the Visual Analogue Scale was used. The Brazilian version of the SF-36 Quality of Life Questionnaire was also applied to assess the patient's subjective perception of her health and the impacts of osteoarthritis on her life. The qualitative and quantitative data were evaluated by regression analysis, to verify whether there was an improvement in the patient's quality of life and well-being. Results: improvement in the ability to perform daily activities, in the analgesic condition, in the stiffness and function of the joints and improvement in physical capacity. Conclusion: Hydrokinesiotherapy offers a safe and effective approach for treating osteoarthritis and promoting the well-being and quality of life of affected patients. The combination of improved physical function and reduced pain during treatment due to less impact on joints due to buoyancy and a generally more pleasant experience in the aquatic environment make hydrokinesiotherapy a valuable therapeutic option for people living with osteoarthritis.